Biological effects of paenilamicin, a secondary metabolite antibiotic produced by the honey bee pathogenic bacterium Paenibacillus larvae. Issue 5 (16th July 2014) - Garcia‐Gonzalez, Eva; Müller, Sebastian; Hertlein, Gillian; Heid, Nina; Süssmuth, Roderich D.; Genersch, Elke
Abstract Paenibacillus larvae is the etiological agent of American Foulbrood (AFB) a world‐wide distributed devastating disease of the honey bee brood. Previous comparative genome analysis and more recently, the elucidation of the bacterial genome, provided evidence that this bacterium harbors putative functional nonribosomal peptide synthetases (NRPSs) and polyketide synthases (PKSs) and therefore, might produce nonribosomal peptides (NRPs) and polyketides (PKs). Such biosynthesis products have been shown to display a wide‐range of biological activities such as antibacterial, antifungal or cytotoxic activity. Herein we present an in silico analysis of the first NRPS/PKS hybrid of P. larvae and we show the involvement of this cluster in the production of a compound named paenilamicin (Pam). For the characterization of its in vitro and in vivo bioactivity, a knock‐out mutant strain lacking the production of Pam was constructed and subsequently compared to wild‐type species. This led to the identification of Pam by mass spectrometry. Purified Pam‐fractions showed not only antibacterial but also antifungal and cytotoxic activities. The latter suggested a direct effect of Pam on honey bee larval death which could, however, not be corroborated in laboratory infection assays. Bee larvae infected with the non‐producing Pam strain showed no decrease in larval mortality, but a delay in the onset of larval death. We propose that Pam, although not essential for larval mortality, is a virulence factor of P. larvae influencing the time course of disease. These findings are not only of significance in elucidating and understanding host–pathogen interactions but also within the context of the quest for new compounds with antibiotic activity for drug development.